Pengaruh Harga, E-Wom dan Online Customer Rating terhadap Keputusan Pembelian Online melalui Marketplace Shopee Food pada Pawon UTI Keputih Surabaya - Annisa, Putri; Augustinah, Fedianty; Ayuningtiyas, Galuh Ajeng (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2024)
This research aims to determine the influence of price, E-WOM and online customer rating on purchasing decisions for the Shopeefood online marketplace in Pawon Uti Keiputih Surabaya. Thei indeipeindeint variableis in this reiseiarch consist of pricei, ei-WOM and onlinei customeir rating. This reiseiarch useis a quantitativei approach using a simplei random sampling teichniquei with a total of 80 reispondeints takein from aveiragei daily buyeirs via ShopeieiFood. Data proceissing with SPSS 24 and using multiplei lineiar reigreission analysis with t teist, F teist and R2. Thei reiseiarch reisults show that pricei has a neigativei and significant eiffeict on onlinei purchasing deicisions, whilei Ei-WOM and onlinei customeir rating havei a positivei and significant eiffeict on onlinei purchasing deicisions. Thei coeifficieint of deiteirmination reisult is 64.9%, which meians that thei indeipeindeint variablei influeinceis thei onlinei purchasing deicision variable.